Teknik REBT (Rational Emotive Behavior Therapy) untuk Mengatasi Kecanduan Game Online pada Siswa Kelas VIII SMP Negeri 14 Bandar Lampung - Diswantika, Noviana; Merisa, Merisa (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This research is a guidance and counseling action research (PTBK) which aims to determine whether the problem of online game addiction of class VIII students can be reduced through group counseling with the Rational Emotive Behavior Therapy (REBT) technique. The subjects of this study were students of class VIII A, totaling 31 students of SMP Negeri 14 Bandar Lampungr. Determination of the subject of this study as many as 5 students, students' online game addiction to 5 students has a high category. Through the results of observations made in the early stages, it was found that 5 students had problems with high online game addiction in students. Then after being given services with the Rational Emotive Behavior Therapy (REBT) technique which was carried out in group counseling, it was seen that the level of online game addiction was well reduced. This can be addressed with the results of observational data and interviews that have been conducted on students. Thus it can be concluded that the results of the research in the first cycle of a decrease in the level of online game addiction possessed by students through the Rational Emotive Behavior Therapy (REBT) technique, this can be seen from the first cycle the average achievement of the online game addiction level of 5 students is 47.06% in the medium category and in the second cycle there was a decrease with an average of 37.4% in the low category.